2022
DOI: 10.3390/life12081164
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hypoxia-Ischemia on Neurogenesis and Structural and Functional Outcomes in a Mild–Moderate Neonatal Hypoxia-Ischemia Brain Injury Model

Abstract: Hypoxic-ischemic encephalopathy (HIE) is a common type of brain injury caused by a lack of oxygen and blood flow to the brain during the perinatal period. The incidence of HIE is approximately 2–3 cases per 1000 live births in high-income settings; while in low- and middle-income countries, the incidence is 3–10-fold higher. Therapeutic hypothermia (TH) is the current standard treatment for neonates affected by moderate–severe HIE. However, more than 50% of all infants with suspected HIE have mild encephalopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…However, compared to the pooled HI/saline control, we found a significant neuroprotective treatment effect with a probability of efficacy of more than 97%. As explained in the statistical methods, this difference can be explained by the individual variability of treatment efficacy in the original experiment compared to the widespread variability of the pooled HI/saline group 20 , 53 , 54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared to the pooled HI/saline control, we found a significant neuroprotective treatment effect with a probability of efficacy of more than 97%. As explained in the statistical methods, this difference can be explained by the individual variability of treatment efficacy in the original experiment compared to the widespread variability of the pooled HI/saline group 20 , 53 , 54 .…”
Section: Discussionmentioning
confidence: 99%
“…We show here that Iodide at a concentration of 3 mg/kg administrated after ligation followed by two more maintenance doses every 24 h (Table 1 ) is neuroprotective following our well-established HI brain injury model, when compared against the pooled HI/saline group, with a probability of efficacy of 98.0%, whilst it was not considered neuroprotective when compared to the matched control group. Again, as explained in the statistical methods this difference can be explained by the individual variability of treatment efficacy in the original experiment compared to the widespread variability of the pooled HI/saline group 20 , 53 , 54 . Further experimental studies are needed to investigate the neuroprotective potency of Iodide.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of reliable indicators to reflect the prognosis after the end of the 72-h continuous treatment is also an urgent problem to be solved ( Garcia-Alix et al, 2023 ). The lack of good therapeutic effects in mild HIBD patients ( Ehlting et al, 2022 ), differences in treatment effects between male and female rats ( Saadat et al, 2023 ), and other instabilities are driving research into the pathogenesis of HIBD, with the hope of proposing new targets to supplement and compensate for the shortcomings of hypothermia therapy. Our study elucidates that GluN2B plays a neuroprotective role in early development by inhibiting excessive activation of the PERK/eIF2α pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The GO analysis indicated that the downregulated DEGs were mainly associated with biological processes related to nervous system development, neuron generation, and neurogenesis. Increasing evidence has demonstrated that the disruption of neurogenesis in the hippocampus significantly contributes to the development of cognitive impairment following neonatal HIBD 35,36 . The activation of the BDNF/TrkB signaling pathway plays a crucial role in reducing cell death in the vicinity of lesions, repairing neuronal damage, and facilitating neurogenesis 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that the disruption of neurogenesis in the hippocampus significantly contributes to the development of cognitive impairment following neonatal HIBD. 35 , 36 The activation of the BDNF/TrkB signaling pathway plays a crucial role in reducing cell death in the vicinity of lesions, repairing neuronal damage, and facilitating neurogenesis. 37 To identify a potential therapeutic target for treating neonatal HIBD, we investigated the neuroprotective effects of DEX on neurogenesis in the hippocampus through the BDNF/TrkB pathway.…”
Section: Discussionmentioning
confidence: 99%